(untitled) (Abstracta, 2022)
Artigos publicados - P134-2022 à P210-2022 Errata - E001-2022 Capítulo de livro - L001-2022 Defesas de Dissertações do IFGW - D013-2022 à D19-2022 Defesas de Teses do IFGW - T011-2022 à T15-2022